Quaking Inhibits Doxorubicin-Mediated Cardiotoxicity Through Regulation of Cardiac Circular RNA Expression - Gupta, Shashi Kumar; Garg, Ankita; Bär, Christian; Chatterjee, Shambhabi; Foinquinos, Ariana; Milting, Hendrik; Streckfuß-Bömeke, Katrin; Fiedler, Jan; Thum, Thomas (Circulation research, 2018)
RBPs (RNA-binding proteins) have been described to be expressed and regulated in various organs including the heart. Little is known about the role of RBPs in heart failure induced by the chemotherapy drug doxorubicin and their interaction with circular RNAs. We aimed to identify key RBPs involved in doxorubicin-mediated heart failure and to elucidate their function. Global transcriptome profiling from murine myocardium exposed to doxorubicin identified 5 differentially expressed RBPs. Expression of the RBP QKI (Quaking) in response to doxorubicin was strongly downregulated in rodent cardiomyocytes and human induced pluripotent stem cell-derived cardiomyocytes in vitro and in vivo in mice. Knockdown of in primary cardiomyocytes increased apoptosis and atrophy after treatment with doxorubicin, whereas lentiviral mediated overexpression of inhibited the doxorubicin-induced apoptosis in cardiomyocytes. In vivo, AAV9 (adeno-associated virus serotype 9)-mediated cardiac overexpression of prevented cardiac apoptosis and cardiac atrophy induced by doxorubicin and improved cardiac function. Mechanistically, by lentiviral-based overexpression and CRISPR/Cas9-mediated silencing of , we identified regulated expression of specific circular RNAs derived from (Titin), (Formin homology 2 domain containing 3), and (Striatin, calmodulin-binding protein 3). Moreover, inhibition of -derived circular RNA increased the susceptibility of cardiomyocytes to doxorubicin. We here show that overexpression of strongly attenuates the toxic effect of doxorubicin via regulating a set of circular RNAs. is, thus, an interesting target molecule to combat doxorubicin-induced cardiotoxicity.